ANTIMICROBIAL AND PHYTOCHEMICAL ANALYSIS ON EXTRACTS OF Moringa oleifera Seeds COLLECTED AT THE UNIVERSITY OF ILORIN BOTANICAL CENTER, KWARA STATE, NIGERIA - Ofesi, Anna O.; Igere, Bright E.; Onoriasakpobare, Felix O.; Chukwuka, Ewere G. (FUDMA JOURNAL OF SCIENCES, 2025)
There had been a rise in the research interest on alternative potential therapeutic agents with specific focus on natural occurring bioactive agents. One of such widely source are seeds of Moringa oleifera, which has buffered phytomedical relevance of the plant. The study evaluates an antimicrobial and phytochemical assessment on extracts of M. oleifera seeds at the University of Ilorin Botanical center, Kwara State, Nigeria. It employed phytochemical analysis of the extracts using both cold ethanolic and N-hexane extracts. A brief standard microbiological/antimicrobial susceptibility testing (using agar well diffusion) was applied as infected wound microbial potential pathogens used were both bacterial and fungus. The presumptively identified bacterial strains used include: Staphylococcus aureus, Escherichia coli, Bacillus subtilis, Pseudomonas aeruginosa while the fungi strain is Aspergillus niger. Our report showed presence of saponins, flavonoids, tannins, and alkaloids in both extraction-solvents used. The four strains used were highly senceptible to M. oleifera seed crude extracts at 150 mg/ml and 200 mg/ml concentration, among which P. aeruginosa showed least sensitivity even at highest concentration of extract in comparison with the antibiotics used as control (ciprofloxacin). It is indicative that extracts of M. oleifera seeds possess relevant therapeutic components and shown the antioxidant property due to the presence of specific antioxidising properties. The results of this study have shown the potentials of M. oleifera seed extracts as a good antimicrobial lead agent since it inhibit orthopaedic wound associated potential pathogens which suggest their therapeutic relevance in disease control cases.